A critical appraisal of the clinical pharmacokinetics of isoniazid - Parkin, Donald Pysden (Stellenbosch : University of Stellenbosch, 2007)
Thesis (PhD (Medicine. Pharmacology))--University of Stellenbosch, 1996.